1999
DOI: 10.1029/1999jd900437
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of dynamic scaling in space‐time rainfall

Abstract: Abstract. As in any evolving process, including rainfall, variability in space and time are not independent of each other but depend in a way particular to the process at hand. Understanding and quantifying the space-time dependences in a process over a range of scales is not always easy because these dependences may be hidden under complex patterns with pronounced statistical variability at all scales. In this paper, we report our efforts to understand the spatiotemporal organization of rainfall at a range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 20 publications
0
91
0
Order By: Relevance
“…The top cascade levels (0, 1 and 2) represent the low spatial frequencies (large precipitation structures), while the bottom cascade levels (5, 6, 7) represent the high spatial frequencies (small precipitation structures). Another important behavior of rainfall fields is known as dynamic scaling, which is the empirical observation that the rate of temporal development of rainfall structures is a power law function of their spatial scale (Venugopal et al, 1999;. This means that large precipitation features are more persistent and hence predictable compared with small precipitation cells, which is closely related to the concept of scaledependence of the predictability of precipitation (Germann and Zawadzki, 2002;Turner et al, 2004).…”
Section: Steps Descriptionmentioning
confidence: 99%
“…The top cascade levels (0, 1 and 2) represent the low spatial frequencies (large precipitation structures), while the bottom cascade levels (5, 6, 7) represent the high spatial frequencies (small precipitation structures). Another important behavior of rainfall fields is known as dynamic scaling, which is the empirical observation that the rate of temporal development of rainfall structures is a power law function of their spatial scale (Venugopal et al, 1999;. This means that large precipitation features are more persistent and hence predictable compared with small precipitation cells, which is closely related to the concept of scaledependence of the predictability of precipitation (Germann and Zawadzki, 2002;Turner et al, 2004).…”
Section: Steps Descriptionmentioning
confidence: 99%
“…With respect to rainfall, Lovejoy and Schertzer [1991], Tessier et al [1993], and Marsan et al [1996] have demonstrated the presence of dynamic scaling in rainfall fields, finding a value of the scaling exponent • roughly equal to 2/3. De Michele and Rosso [1999] and Venugopal et al [1999aVenugopal et al [ , 1999b have applied this concept to study the evolution of a rainfall field.…”
Section: I(ta) Arf(t A): I(t A0)'mentioning
confidence: 99%
“…In both systems blending is achieved in physical space and the weight given to the extrapolation component takes the form of a fixed exponential decay with time. Later works (Venugopal et al, 1999;Germann and Zawadzki, 2002) have shown that predictability of rainfall structures has a scale-dependence based on dynamic scaling processes. In the Short-Term Ensemble Prediction System (STEPS, see Bowler et al, 2006) the merging of the extrapolation and NWP component forecasts is performed in a scale-dependent way using several levels on cascade processes.…”
Section: Introductionmentioning
confidence: 99%